(untitled) - Michaelides, Alex; 1977- (New York, 2019)
Alicia Berenson's life is seemingly perfect. A famous painter married to an in-demand fashion photographer, she lives in a grand house with big windows overlooking a park in one of London's most desirable areas. One evening her husband Gabriel returns home late from a fashion shoot, and Alicia shoots him five times in the face, and then never speaks another word. Alicia's refusal to talk or give any kind of explanation turns a domestic tragedy into something far grander, a mystery that captures the public imagination and casts Alicia into notoriety. The price of her art skyrockets, and she, the silent patient, is hidden away from the spotlight of the tabloids at the Grove, a secure forensic unit in North London. Theo Faber is a criminal psychotherapist who has waited a long time for the opportunity to work with Alicia. His search for the truth leads him down a terrifying path and threatens to consume him.
Keywords: Investigation; Murder; Fiction; Crimes against; Married people; Husbands; Fiction; Fiction; Fiction; London (England); Psychological fiction; Thrillers (Fiction)